Static and Dynamic Slope Stability Analysis for Non-Commercial Nuclear Power Site - Nur, Siti Hijraini; Hafid, Abdul (Departemen Teknik Sistem Perkapalan, Universitas Hasanuddin, 2023)
This paper discuss slope stability problems both static and dynamic analysis in Non-Commercial Nuclear Power site. Soil exploration and number series of test were made to assist in preparing design, carried out input parameter for SLOPE/W model with Morgenstern-Price method. Morgenstern-Price method considers both shear and normal forces, satisfies both moment and force equilibrium, and allows for a variety of user-selected interslice force function. Slope stability analysis results in static modeling conditions relatively safe with the number of safety factors are 2.937 for normal condition and 2.292 when ground water table increase. In the condition of earthquake loads of the 1000-year period with a ground level peak acceleration value of 0.406 g, safety factor value analysis dropped to 0.914. Dynamic Slope stability analysis results pore ​​water pressure shows a different pattern compared to the initial conditions at 0 seconds, total stress pattern does not change, while the vertical effective stress and displacement pattern changes very significantly.